Carbon Paste Electrode Modified Zeolite-Iron as a Chromium(VI) Detection Medium - Arif, Zulhan; Agustina, Rofiqoh Inayati; Rahmawati, Heni; Aini, Nazwa Aisyah; Rohaeti, Eti (Indonesian Journal of Chemical Studies, 2024)
Chromium exists in two dominant species in nature, Cr(III) and Cr(VI). Both are stable; however, Cr(VI) exhibits significantly higher toxicity than Cr(III). Existing measurement methods could not differentiate between these two chromium species. Therefore, a more sensitive and selective measurement method was required for their speciation, particularly for Cr(VI) detection. In this study, a carbon paste electrode modified with zeolite and iron was developed for Cr(VI) measurement using the voltammetry method. The electrode was prepared by mixing graphite, iron-modified zeolite, and liquid paraffin. Measurements were conducted using cyclic voltammetry within a potential range of -1.2 V to 1.2 V. A 0.05 M KCl solution was used as the electrolyte. Electrode characterization was carried out concerning three parameters: the effect of analyte pH, preconcentration time, and the composition of iron-modified zeolite. The optimum Cr(VI) measurement was achieved in a 50 μM Cr(VI) solution at pH 3 using a carbon paste electrode with 20% iron-modified zeolite and a preconcentration time of 25 min. Under these optimal conditions, a cathodic peak current of 5.22 μA was obtained.